2016
DOI: 10.1121/1.4938237
|View full text |Cite
|
Sign up to set email alerts
|

Is low frequency ocean sound increasing globally?

Abstract: Low frequency sound has increased in the Northeast Pacific Ocean over the past 60 yr [Ross (1993) Acoust. Bull. 18, 5–8; (2005) IEEE J. Ocean. Eng. 30, 257–261; Andrew, Howe, Mercer, and Dzieciuch (2002) J. Acoust. Soc. Am. 129, 642–651; McDonald, Hildebrand, and Wiggins (2006) J. Acoust. Soc. Am. 120, 711–717; Chapman and Price (2011) J. Acoust. Soc. Am. 129, EL161–EL165] and in the Indian Ocean over the past decade, [Miksis-Olds, Bradley, and Niu (2013) J. Acoust. Soc. Am. 134, 3464–3475]. More recently, And… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 31 publications
0
38
0
1
Order By: Relevance
“…Contrary to what is expected and generally observed [42], the deep water ambient noise level measured at our stations in the 40–60 Hz frequency band is decreasing from 2010 to 2015, especially at MAD and NEAMS sites. This notable decrease is not totally surprising, since a similar observation is made in the South Atlantic Ocean [43]. However, at Diego Garcia Island, ambient noise in the 40–60 Hz frequency-band has been increasing in the past decades [29].…”
Section: Discussionmentioning
confidence: 65%
“…Contrary to what is expected and generally observed [42], the deep water ambient noise level measured at our stations in the 40–60 Hz frequency band is decreasing from 2010 to 2015, especially at MAD and NEAMS sites. This notable decrease is not totally surprising, since a similar observation is made in the South Atlantic Ocean [43]. However, at Diego Garcia Island, ambient noise in the 40–60 Hz frequency-band has been increasing in the past decades [29].…”
Section: Discussionmentioning
confidence: 65%
“…In the southern Indian Ocean, however, unlike in other parts of the world ocean, the ambient noise level tends to slightly decrease over the years, at the different frequency bands bracketing the targeted call units (Figure ; see also Miksis‐Olds & Nichols, ). This observation could suggest that in the southern Indian Ocean, the long‐term call frequency decline is caused by a decrease in the ambient noise level.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term measurements from deep-water sites in the Northeast Pacific have shown that low-frequency (<~50 Hz) noise levels in that ocean basin increased markedly (by ~10 dB) between the 1960 s and mid-1990 s1112. Since then, this trend has largely levelled off or begun to decline13, and data from the past decade suggest that more recent trends in noise levels for other ocean basins may also be mixed14. The extent to which these open-ocean trends apply to the shallower continental shelf seas where human activity is concentrated is unclear15, since long-term datasets for these regions are lacking.…”
mentioning
confidence: 99%